The regional embeddedness of small manufacturing and service firms: regional networking as knowledge source for innovation? - Knut Koschatzky; Andrea Zenker (Fraunhofer-Institut für System- und Innovationsforschung ISI, 1999)
Information and knowledge are important prerequisites for innovation activity in firms. One important means of acquiring coplementary knowledge are innovation networks. Depending on their absortive capacity and knowledge base, firms develop different abilities to access and utilise external knowledge. These abilities might also be linked to firm size. Although size as such is not a decisive criterion for distinguishing between the innovative performance of firms, it can at least be used to classify firms according to common structural characteristics. It is objective of this paper to analyse whether the size of a firm significantly affects its innovative behaviour and cooperation pattern and whether there are differences between manufacturing firms and business-related service firms. Using data from a regional innovation survey carried out in Germany, we come to the conclusion that for structural firm characteristics, innovation strategies, information use and innovation network size matters. Small manufacturing and service firms mainly behave similar and are more regionally orientated in their market reach and knowledge acquisition than large firms- Especially small firms in intermediate and rural areas strongly depend on regionally available knowledge sources and are therefore discriminated compared to large firms which make a more frequent use of knowledge and information sources from outside the region.
urn:nbn:de:0011-n-17716
Keywords: 330; Klein- und Mittelunternehmen; Innovationsmanagement; Unternehmenskooperation; Business Network; Forschungskooperation; Region; Verarbeitendes Gewerbe; Dienstleistungssektor; Deutschland